Congressional social media communications: evaluating Senate Twitter usage. Issue 5 (12th September 2016) - Straus, Jacob R.; Williams, Raymond T.; Shogan, Colleen J.; Glassman, Matthew E.
Abstract : Purpose: The purpose of this paper is to understand why some Senators choose to use Twitter more frequently than others. Building on past research, which explored causal factors leading to early congressional adoption, theories about why some Senators use Twitter more frequently in their daily communications strategies are developed. Design/methodology/approach: A "power user" score was developed by evaluating each Senator's clout, interactivity, and originality on Twitter. These scores are then used as the dependent variable in a regression model to evaluate which factors influence Senators becoming Twitter "power users." Findings: The study found that: constituent income is positively correlated with heavy use, but constituent education level is not; the more ideological a Senator is the more he or she will be a Twitter power user; the number of days on Twitter is a significant indicator of advanced Twitter usage; and having staff dedicated to social media is positively correlated with being a Twitter power user. Research limitations/implications: All Senators in the second session of the 113th Congress (2014) were evaluated. As such, future research hope to expand the data set to additional Senators or the House of Representatives. Practical implications: A better understanding of why some Senators use Twitter more than others allows insight into constituent communications strategies and the potential implications of real-time communication on representation, and the role of accountability between a Senator and his or her constituents. Originality/value: The study examines constituent communication by Senators in a new, more interactive medium than previously considered. Additionally, the study places findings about Senator's constituent communication in the broader context of representation.